The Development of Photo-Tourism in Samarkand - Azgarov Abdumutalib; Alisher O’G’li, (Indonesian Journal of Law and Economics Review, 2020)
In these days, tourism is rapidly gaining more and more popularity in the world, this raises the problem of congestion in many popular tourist regions, while many other regions remain impassable, unknown and unpopular. The development of globalization has significantly expanded the world tourism market, the number of tourists, the variety and number of tourist products, the geography of travel destinations, the latest tourism technologies are developing, new travel companies are appearing. In this regard, in order to reduce the problem of congestion in relevant tourist regions, it becomes necessary to promote those territories that are unpopular and unrecognizable in our time and about which too little information has been collected. Also, there has a problem related to finance of tourists: In most cases, they cannot let themselves to go to places they want. A completely new, only contagious type of tourism can solve this problem – Photo-tourism, thanks to which tourists will be able to see the whole diversity of natural, cultural and historical tourist regions and places. The purpose of the article is to determine the relevance of the promotion of tourist areas using the type of tourism as photo-tourism. To investigate the types of photo-tourism, to define the concepts and methods of implementing the promotion of territories using photo-tourism. The article discusses the features of photo-tourism, identifies areas of its development and attractive events, festivals in the Samarkand, identifies the target audience, identifies environmental criteria for creating high-quality photos, and analyzes the photo-tourism market in Uzbekistan.